The development of a system to identify basic 2D shape / Azizah Ahmad - Ahmad, Azizah (2006)
This paper presents a study on identifying 2D shapes using Image Processing and Artificial Neural Network as the main analyzing tools. There were three basic type of shapes that were analyzed in this study; circle, rectangular and triangle. In order to obtain the image, webcam was used to capture the image. Image Processing tools were used to process the image before being sent to the Artificial Neural Network for the identification process.